THE GENUS AS, A POTENTIAL SOURCE OF ANTICANCER AGENT: AN UPDATED REVIEW (Baqai Journal of Health Sciences)
On the list of the world's most significant health problems, cancer rates are high. As a consequence, cancer treatment is a global priority. A cell may acquire malignant characteristics by learning how to avoid apoptosis. Defects in regulating apoptotic pathways enable cancer cells to become chemoresistant, highlighting the need to develop new anti-apoptotic drugs to combat the disease. Apoptosis can be induced by inhibiting anti-apoptotic factors or by activating pro-apoptotic molecules. However, the adverse side effects of chemotherapy have prompted researchers to investigate whether medicinal plants could replace chemotherapy in cancer treatment. Pistachios have antioxidant, antifungal, antimicrobial, and anticancer properties, among many other pharmacological benefits. The ability of pistachios to inhibit tumor growth is supported by data indicating that they do so by modulating multiple apoptotic pathways in tumor cells. This article introduces pistachios and discusses their potential anticancer effects, mainly targeting apoptosis related pathways